Cyst nematode bio-communication with plants: implications for novel management approaches - Ochola, J.; Coyne, D.; Cortada Gonzales, L.; Haukeland, Solveig; Ng'ang'a, M.; Hassanali, A.; Opperman, C.; Torto, B. (Wiley, 2021)
Bio‐communication occurs when living organisms interact with each other, facilitated by the exchange of signals including visual, auditory, tactile and chemical. The most common form of bio‐communication between organisms is mediated by chemical signals, commonly referred to as ‘semiochemicals’, and it involves an emitter releasing the chemical signal that is detected by a receiver leading to a phenotypic response in the latter organism. The quality and quantity of the chemical signal released may be influenced by abiotic and biotic factors. Bio‐communication has been reported to occur in both above‐ and below‐ground interactions and it can be exploited for the management of pests, such as cyst nematodes, which are pervasive soil‐borne pests that cause significant crop production losses worldwide. Cyst nematode hatching and successful infection of hosts are biological processes that are largely influenced by semiochemicals including hatching stimulators, hatching inhibitors, attractants and repellents. These semiochemicals can be used to disrupt interactions between host plants and cyst nematodes. Advances in RNAi techniques such as host‐induced gene silencing to interfere with cyst nematode hatching and host location can also be exploited for development of synthetic resistant host cultivars. © 2020 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.